2016
DOI: 10.1038/jhg.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high frequency of mutations in a breast and/or ovarian cancer cohort: implications of embracing a multi-gene panel in molecular diagnosis in India

Abstract: Breast and/or ovarian cancer (BOC) are among the most frequently diagnosed forms of hereditary cancers and leading cause of death in India. This emphasizes on the need for a cost-effective method for early detection of these cancers. We sequenced 141 unrelated patients and families with BOC using the TruSight Cancer panel, which includes 13 genes strongly associated with risk of inherited BOC. Multi-gene sequencing was done on the Illumina MiSeq platform. Genetic variations were identified using the Strand NGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 39 publications
8
67
2
Order By: Relevance
“…26 The same mutation was reported in three patients by Mannan et al 19 suggesting that there may be a common ancestry or they migrated from the same place.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…26 The same mutation was reported in three patients by Mannan et al 19 suggesting that there may be a common ancestry or they migrated from the same place.…”
Section: Discussionmentioning
confidence: 65%
“…18 A recent paper from a company offering sequencing in India showed that occurrence of BRCA mutations in their cases was 36.2%, but this high percentage may be due to the reason that the cases sent for BRCA1 and 2 analysis to the company were mostly of familial type, unlike this study where all cases presenting with BC were used for percentage analysis. 19 Founder mutations are specific sequence variations which appear repeatedly in ethnically defined groups because of shared common ancestry. This effect explains the high frequencies of disease-associated mutations in specific human populations.…”
Section: Discussionmentioning
confidence: 99%
“…The GG allele was the most frequent similar to European Caucasian population [29]. A characteristic insertion (T>TA) in exon 18 was also found in most of patients (homozygous TA/TA in patients IDs 1,2,4,7,8,9,10,11,13,14,15,16,17,22,23 and 24), (heterozygous T>TA, rs3830355, IVS18-50insA in patients IDs 3, 5,6, 12 and 18). Both PDGFRA exon 18 mutation and exon 12 mutation were related more to gastric and intestinal GIST (gastrointestinal tumors) more than to colonic [30].…”
Section: Missense Splicing and Indels Mutationsmentioning
confidence: 93%
“…Only, NRAS, RET and GNA11 showed coverage less than 95% (≤ 20 reads). For library preparation, Trusight panel DNA library preparation protocol (Illumina) was used [13].…”
Section: Trusight Tumor 15 Panel Illumina Crc Panelmentioning
confidence: 99%
“…Genomic DNA was used for the library preparation for NGS as previously described [Mannan et al, 2016] and sequenced on the NextSeq platform (Illumina) according to the manufacturer's instructions. Variations were identified using the STRAND ® NGS software and imported into StrandOmics TM , a proprietary clinical genomics interpretation and reporting platform.…”
Section: Methodsmentioning
confidence: 99%